Sekatenan Tradition as a Form of Community Integration in the Viewpoint of Phenomenology and Sociology of Religion - Mushbihah Rodliyatun; Badrus Zaman (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2022)
This study aims to examine the relationship between religious practice and the beliefs of the people who celebrate it, namely the Sekatenan ceremony, which is part of the grebeg maulud event, by explaining the phenomenon of cultural activity at the Yogyakarta Palace, the form of organization in the sekaten tradition from the point of view of phenomenology and the sociology of religion. This type of research is qualitative, using data triangulation techniques with observation, interviews, and documentation methods. The approach used in phenomenology and the sociology of religion. The results of his research show that the study of religious phenomena assumes that diversity can only be understood in its entirety which is centered on the essential nature of religious life, Sekatenan has symbolic meaning and behavior that contains values ​​including religion and culture. Based on sociological studies, Sekatenan has become a community tradition in the Yogyakarta area. Religious activities explain religious issues, which are always associated with sociological aspects. The Sekatenan ceremony can establish a good relationship between visitors, community members, and traders, fellow traders, and the local government with the palace so that the objectives can be achieved to improve the social quality of community life.